Application of Higher Order Hopfield Network - Saratha, Sathasivam; Ng, Pei Fen; Muraly, Velavan (ENCON 2013, 2013)
Neural network and logic integration is the latest trend in Artificial Intelligence. Neural Symbolic Integration is a combination of neural networks’ robust learning capabilities with symbolic knowledge representation, reasoning, and explanation capabilities in ways that retain the strengths of each paradigm. In this paper, an Agent Based Modelling (ABM) was introduced by using Netlogo which carry out higher order horn clauses in Hopfield network. Our interest in this paper is confined largely to an important class of neural networks that perform useful computations through a process of learning. So, from the ABM that designed, we can carry out some computer simulation to verify and test the ABM develop.